Impact of Traces of Hydrogen Sulfide on the Efficiency of Ziegler–Natta Catalyst on the Final Properties of Polypropylene (2022)
Sulfur compounds are removed from propylene through purification processes. However, these processes are not 100% effective, so low concentrations of compounds such as H2S may be present in polymer-grade propylene. This article studies the effects of H2S content on polypropylene polymerization through the controlled dosage of this compound with concentrations between 0.07 and 5 ppm and its monitoring during the process to determine possible reaction mechanisms and evaluate variations in properties of the material by TGA, FTIR, MFI, and XDR analysis. It was found that the fluidity index increases directly proportional to the concentration of H2S. In addition, the thermo oxidative degradation is explained by means of the proposed reaction mechanisms of the active center of the Ziegler–Natta catalyst with the H2S molecule and the formation of substances with functional groups such as alcohol, ketones, aldehydes, CO, and CO2 by the oxidation of radical complexes. This study shows for the first time a reaction mechanism between the active center formed for polymerization and H2S, in addition to showing how trace impurities in the raw materials can affect the process, highlighting the importance of optimizing the processes of removal and purification of polymer-grade materials